Investigation on Flame Characteristics of a Flameless Combustor Ignition System Using Spiral Nozzle - AHMAD LAZIM, AMIRUL HAFIZI; KASANI, ADAM (Progress in Engineering Application and Technology, 2023)
Nowadays, combustion is one of the industrial procedures for heating, drying, shrinking, and polymerizing. Combustion generates hot air, which is subsequently channelled to selected locations for utilisation. The purpose of this study was to discover and learn about the fire characteristics that occur when a spiral nozzle is utilised. The challenge of initiating the fire in the combustor chamber was one of them. The research objectives are as follows: to establish the best operating method for igniting and firing up the combustor chamber. Experiments were carried out in the automobile lab of the Faculty of Mechanical and Manufacturing Engineering FKMP during the project’s preliminary testing. To conduct out this investigation. This experiment was carried out using premixing (air pressure and Liquefied Petroleum Gas (LPG) and air pressure). For this experiment, an aapparatus such as 1 LPG gas barrel, an air compressor, pipe tubing size 10, 2 flow metres for air and LPG gas, a spiral nozzle 12 inch, and a blow torch to light the fire. Five thermocouples were employed, with a 5 cm space between them. Researchers will be able to overcome the firing up problem during preheating as a result of this research. damaging to the environment. The use of flameless combustion will help to extend the life of the equipment by ensuring that there is no flame present in the combustion chamber.